The Draft Assembly of the Radically Organized Stylonychia lemnae Macronuclear Genome - Aeschlimann, Samuel H. (Oxford University Press, 2014)
Stylonychia lemnae is a classical model single-celled eukaryote, and a quintessential ciliate typified by dimorphic nuclei: A small, germline micronucleus and a massive, vegetative macronucleus. The genome within Stylonychia’s macronucleus has a very unusual architecture, comprised variably and highly amplified “nanochromosomes,” each usually encoding a single gene with a minimal amount of surrounding noncoding DNA. As only a tiny fraction of the Stylonychia genes has been sequenced, and to promote research using this organism, we sequenced its macronuclear genome. We report the analysis of the 50.2-Mb draft S. lemnae macronuclear genome assembly, containing in excess of 16,000 complete nanochromosomes, assembled as less than 20,000 contigs. We found considerable conservation of fundamental genomic properties between S. lemnae and its close relative, Oxytricha trifallax, including nanochromosomal gene synteny, alternative fragmentation, and copy number. Protein domain searches in Stylonychia revealed two new telomere-binding protein homologs and the presence of linker histones. Among the diverse histone variants of S. lemnae and O. trifallax, we found divergent, coexpressed variants corresponding to four of the five core nucleosomal proteins (H1.2, H2A.6, H2B.4, and H3.7) suggesting that these ciliates may possess specialized nucleosomes involved in genome processing during nuclear differentiation. The assembly of the S. lemnae macronuclear genome demonstrates that largely complete, well-assembled highly fragmented genomes of similar size and complexity may be produced from one library and lane of Illumina HiSeq 2000 shotgun sequencing. The provision of the S. lemnae macronuclear genome sets the stage for future detailed experimental studies of chromatin-mediated, RNA-guided developmental genome rearrangements.